Effect of Supplementing Wet Distillers’ Grains with Solubles to Maize Silage Based Diet on Performance of Growing Nellore Jodipi Ram Lambs - Naveena, K; Ravi, A.; Devasena, B.; Shakila, S. (Indian Journal of Animal Nutrition, 2020)
The objective of the study was to evaluate performance of ram lambs supplemented with distillers grains with solubles (DGS) under intensive system. In a completely randomized design, 24 growing Nellore Jodipi ram lambs were divided into 4 equal groups of six each. Corn silage was fed ad libitum to all the rams, basal diet was supplemented with DDGS at 1.0% BW in control group (T1), whereas WDGS was supplemented at 1.0, 1.5 and 2.0 % BW in groupsT2, T3 and T4, respectively.The average daily gain (g) of 105.4, 69.1, 81.6, and 89.5 was recorded recorded in T1 to T4 fed lambs respectively, was higher (P<0.05) in T1 than in T2. The DMI from silage and total DMI were not significantly different among treatments. The DMI (g/d) from dry DGS was 153.0 in T1 and 46.6, 74.4 and 99.8, in T2 to T4 from wet DGS, respectively and was higher (P<0.05) in T1 than in T2. The feed efficiency was inferior (P<0.05) in T2 as compared to other treatments. The digestibility of nutrients except CP and EE was not significantly different among treatments. The N retained as per cent of intake and the molar proportion of acetate, and acetate to propionate ratio was higher (P<0.05) in T1 than in other treatments. There was no significant difference among treatments with respect to serum concentration of protein, mineral profile of serum except for a higher (P<0.05) phosphorus in T1 fed lambs. The carcass traits, chemical composition and mineral profile of longissimus dorsi muscle were also not significantly different among dietary treatments. Returns over feed cost was higher (P<0.01) in T1 and T4, than in T2 and T3 fed lambs. It was concluded that supplementation of wet DGS to maize silage-based diet at 2.0% of body weight resulted in performance comparable with dry DGS supplementation at 1 % of body weight.